Response of Zea mays to multimetal contaminated soils a multibiomarker approach - Tovar-Sánchez, Efraín (Ecotoxicology (London, England), 2018)
Heavy metals present in mine tailings pollute agroecosystems, put the integrity of the environment at risk and become a major route of exposure to humans. The present study was carried out in Taxco, Guerrero, Mexico, where millions of tons of mine tailings have been deposited. Soils from this region are used for agricultural activities. Maize (Zea mays) was selected as a test plant, because it is one of the most common and important cereal crops in Mexico and worldwide. Thirteen metals were selected and their bioaccumulation in roots, leaves and fruits were measured in plants cultivated in soils contaminated with mine tailings and those cultivated in non-contaminated soils. The effect of metal bioaccumulation on: macro and micromorphology, size, biomass, coloration leaf patterns and on DNA damage levels in different structures were determined. The bioaccumulation pattern was: root > leaf > fruit, being only Mn and Cr bioaccumulated in all three structures and V in the roots and leaves. A significant effect of metal bioaccumulation on 50% of the size and leaf shape and 55% of the biomass characters in Z. mays exposed plants was detected. Regarding micromorphological characters, a significant effect of metal bioaccumulation on 67% of the leaf characters and on 100% of the color basal leaf characters was noted. The effect of metal bioaccumulation on the induction of DNA damage (leaf > fruit > root) was detected employing single cell gel electrophoresis analysis. An approach, in which multi endpoints are used is necessary to estimate the extent of the detrimental effects of metal pollution on agroecosystem integrity contaminated with mine tailings